1990
DOI: 10.1051/rnd:19900866
|View full text |Cite
|
Sign up to set email alerts
|

Estimation de la teneur en lipides des chèvres laitières par diverses méthodes informant sur le métabolisme lipidique ou l'état corporel

Abstract: Summary ― In 10 lactating goats, the body condition score was well correlated (r = from 0.80 to O.B3) to the empty body lipid content measured chemically after slaughtering. A good evaluation (r = 0.83) can be obtained from the total fatty acid content of oleic acid in milk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…STF was recorded in order to estimate its relationship with body reserves as an eventual alternative anatomical site (sternal region) to lumbar region to assess BCS. In goats, sternal region was found to provide greater precision on the prediction of body reserves than lumbar or caudal regions (Santucci and Maestrini, 1985;Morand-Fehr et al, 1989;Amaro and Caldeira, 1991). The proportion of remaining variation accounted for by STF on the prediction of TF and muscle weights, and on the percentage of TF in EBW (Table 12), showed that sternal region could eventually be an alternative site to evaluate BCS, although it has revealed to be a poorer predictor of body reserves than LJ.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…STF was recorded in order to estimate its relationship with body reserves as an eventual alternative anatomical site (sternal region) to lumbar region to assess BCS. In goats, sternal region was found to provide greater precision on the prediction of body reserves than lumbar or caudal regions (Santucci and Maestrini, 1985;Morand-Fehr et al, 1989;Amaro and Caldeira, 1991). The proportion of remaining variation accounted for by STF on the prediction of TF and muscle weights, and on the percentage of TF in EBW (Table 12), showed that sternal region could eventually be an alternative site to evaluate BCS, although it has revealed to be a poorer predictor of body reserves than LJ.…”
Section: Resultsmentioning
confidence: 99%
“…Lumbar joint (LJ), which is handled to assess BCS, was studied by others authors in order to predict the body composition of ewes (Delfa et al, 1989;Frutos et al, 1997) and goats (Amaro, 1990), as well as sternal fat in goats (Santucci and Maestrini, 1985;Morand-Fehr et al, 1989;Amaro and Caldeira, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Le maintien de l'état corporel est largement assuré pour les brebis ayant reçu une complémentation au pâturage aussi bien en caroube qu'en orge. Ceci s'explique sans doute par les bonnes valeurs énergétiques des deux compléments qui ont permis le maintien, voire une légère augmentation des réserves corporelles en énergie sous forme de lipides, les NEC étant corrélées avec la teneur en lipides de l'organisme entier (Morand-Fehr et al, 1990). effet du régime AlimentAire sur les performAnCes de reproduCtion des brebis Les paramètres de reproduction des brebis en fonction de la nature du complément énergétique sont présentés respectivement dans le tableau III.…”
Section: Composition Chimique Et Valeurs Nutritives Du Pâturage Et Deunclassified